TEORI KONTROL SOSIAL DAN PENANGANAN PERUNDUNGAN TERHADAP ANAK DENGAN DIVERSI DALAM UPAYA PENCEGAHAN PERUNDUNGAN/ BULLYING DI INSTITUSI KAMPUS (Faculty of Law, University of Palembang, 2024)
In persuasive efforts to tackle juvenile delinquency which has an impact on deviant behavior by bullying in campus institutions, it is carried out by using social control theory, where the stages are as follows: Direct control that is given without using restrictive tools and laws, Internalization control that is carried out from within consciously, Indirect control that relates to influential recognition [identification] with parents and other non-criminals and the availability of alternative means and values to achieve goals. The Process of Handling Bullying in Campus Institutions with Diversion as stipulated in Article 1 point 7 of the Child Criminal Justice System Law that Diversion is an effort to transfer the settlement of children's cases from the criminal justice process to a process outside of criminal justice. The concept of Diversion is based on Restorative law. Children as victims, the main focus of the Restorative approach lies in the recovery and compensation of losses. In the mediation process, victims and perpetrators must be accompanied by parents or guardians, community counselors (PK), and professional social workers